Crack resistance of a noble green hydrophobic antimicrobial sealing coating film against environmental corrosion applied on the steel–cement interface for power insulators. Issue 16 (31st March 2022) - Sanyal, Simpy; Chelliah, Ramachandran; Kim, Taeyong; Rabelo, Matheus; Oh, Deog-Hawn; Pham, Duy Phong; Yi, Junsin
Abstract : Due to their great load-bearing capabilities, steel–cement interface structures are commonly employed in construction projects, and power utilities including electric insulators. Abstract : Due to their great load-bearing capabilities, steel–cement interface structures are commonly employed in construction projects, and power utilities including electric insulators. The service life of the steel–cement interface is always decreasing owing to fracture propagation in the cement helped by steel corrosion. In this paper, a noble crack-resistant solution for steel–cement interfaces utilized in hostile outdoor environments is proposed. A Ce-rich, homogeneous, and thick hydrophobic sealing coating (HSC) is developed on the steel–cement interface after 60 minutes of immersion in a 60 000 ppm CeCl3 ·7H2 O sealing coating solution. The specimens treated with optimized HSC film demonstrate fissure filling, lowest corrosion current ( I corr ) 2.3 × 10 −7 A cm −2, maximum hardness (109 Hv), oxide-jacking resistance (40 years), hydrophobic characteristics, carbonation resistance, and bacterial corrosion resistance, resulting in a crack-free steel–cement interface. This work will pave the way for a new branch of environmentally acceptable coatings for the construction and power industries.